1995
DOI: 10.1111/j.1467-6419.1995.tb00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Event Study Methods and Evidence on Their Performance

Abstract: The paper outlines widely used methods of estimating abnormal returns and testing their significance, highlights respects in which they differ conceptually, and reviews research comparing results they produce in various empirical contexts. Direct evidence on the performance of different methods is available from simulation experiments in which known levels of abnormal return are added. The market model is most commonly used to generate expected returns and no better alternative has yet been found despite the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
130
0
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(149 citation statements)
references
References 60 publications
7
130
0
12
Order By: Relevance
“…The first is event study methodology. An event is defined as an announcement by a company (whether external or solely internal), for instance, the announcement of a takeover bid (Armitage, 1995). In the M&A concept, event studies are typically applied to measure the change in stock price in the acquiring and target firms, pre and post the M&A activity announcement.…”
Section: Methodsology Used In Manda Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is event study methodology. An event is defined as an announcement by a company (whether external or solely internal), for instance, the announcement of a takeover bid (Armitage, 1995). In the M&A concept, event studies are typically applied to measure the change in stock price in the acquiring and target firms, pre and post the M&A activity announcement.…”
Section: Methodsology Used In Manda Researchmentioning
confidence: 99%
“…Glascock et al (1991) asserted that it is easier to find out any AR presence if a shorter event period is used. In practice, a two-day event window is most common if the event date can be determined precisely, supplemented by cumulative abnormal returns for longer periods ex and post (Armitage, 1995). If the event date is not straightforward, then it would be better to choose one of the days at random as the event date (Dyckman et al, 1984).…”
Section: Event Study Methodsologymentioning
confidence: 99%
“…One of the most prevalent approaches in event study methodology is the market model, since evidence has suggested that the model will perform in most circumstances, as well as, if not better than any other alternative (Armitage, 1995). Generally, for statistical models, it is required that asset returns be jointly multivariate normal, independent and identically distributed over time, as explained by Campbell, Lo, & MacKinley (1997).…”
Section: Modeling and Estimating Share Price Reactionmentioning
confidence: 99%
“…However, α and β will also become "out of date" due to the longer estimation period. Armitage (1995b) suggested an estimation period of around 100 days is usually appropriate. Brown and Warner (1985) compared the event study using monthly stock returns and daily stock returns.…”
Section: Event Studymentioning
confidence: 99%
“…This is calculated by dividing the event period residuals by the standard deviation of the estimation period residuals corrected by the prediction error. Armitage (1995b) explained the prediction error could arise in two ways. First, the error could arise from the difference between the true regression line and the estimated regression line.…”
mentioning
confidence: 99%